Substitution Between Production Labor and Other Inputs in Unionzed and Nonunionized Manufacturing - Freeman, Richard B.; Medoff, James L. (The Review of Economics and Statistics, 1982)
THE ease of substitution between labor and other factors of production is an important determinant of the elasticity of demand for labor and thus of the economic effects of unionism. All else the same, the greater the elasticity of substitution, the greater is the elasticity of derived demand and the greater the displacement of labor for a given union-induced wage increase. In sectors where this elasticity is large, unions are likely to be relatively weak and able to win only slight wage gains (Freeman and Medoff, 1981 and forthcoming) or, if they win large gains, will have to pay a high price in terms of lost jobs. In the sectors where the elasticity is small, unions may be able to extract a substantial wage premium at little cost in terms of employment. Moreover, as a simple general equilibrium model indicates, the elasticity of substitution between labor and other factors in the unionized sector is a key parameter in determining the impact of the IIunion wage effect on the earnings of nonunion workers and on the efficiency of the economy (Johnson and Mieskowski, 1970). Despite the importance of the elasticity of labor demand for an analysis of unionism, little attention has been given to the absolute and magnitude of this elasticity under collective bargaining. While there is some discussion of technological change and the substitution of capital and nonproduction workers for organized production workers in the institutional literature (e.g., Slichter, 1941; Slichter, Healy and Livernash, 1960; Bok and Dunlop, 1970), modern econometric work provides no estimates of the relevant parameters. As a result, Johnson and Mieskowski (1970), Rees (1963), Lewis (1964) and others have been forced to evaluate union effects with guesstimates of the elasticities of concern in union settings. This paper attempts to fill some of the gap in our knowledge by providing estimates for U.S. manufacturing of the constant output elasticity of demand for unionized and nonunionized production workers and of the elasticity of substitution between these workers and other inputs. The analysis concentrates on what we call the relative inelasticity hypothesis, which states that the demand for production workers will be more inelastic in the presence of a union for two reasons: the likelihood that unions have organized and survived in sectors with low elasticities, and the effects of various contract provisions on the ability of management to substitute other factors for production labor. The study is divided into four sections. Section I develops the rationale for the inelasticity hypothesis and describes the nature of the empirical analysis conducted to test its validity. The second section uses a 1972 state by 2-digit Standard Industrial Classification (SIC) industry data file for manufacturing to estimate the elasticity of substitution between production labor and both nonproduction labor and capital in the union and nonunion sectors of U.S. manufacturing industries. Section III provides estimates, based on a 1968-72 sample of manufacturing establishments, of the elasticity of substitution between production and nonproduction labor (the only two inputs for which information is available). The final section briefly summarizes the findings and discusses their implications for understanding the impact of trade unionism on the U.S. economy. To preview the ensuing discussion, our main conclusion is: Substitution between production labor and other inputs is generally lower in union Received for publication March 6, 1978. Revision accepted for publication August 17, 1981. * Both authors are with Harvard University and the National Bureau of Economic Research. Supported by U.S. Department of Labor Grant No. J-9-M-6-0094, National Science Foundation Grant No. APT77-16279, and the National Bureau of Economic Research (under its program of research on labor economics). We are especially grateful to Jane Mather for her invaluable assistance on this project and to Greg Bialecki, Charles Brown, Gary Chamberlain, Kathy Coons, Jon Fay, Martin Van Denburgh, and Lori Wilson for their significant contributions. The study has not been reviewed by the Board of Directors of the National Bureau.